Innovation in Arabic Language Learning Assessment Based on Kahoot: Systematic Literature Review - Ahmad Khoirur Roziqi; M. Yunus Abu Bakar; Baiq Tuhfatul Unsi (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
Innovation is needed to support the Arabic language learning process carried out online. One form of this innovation can be realized through the use of learning media. Learning media play a role in arousing students' motivation and enthusiasm for learning, which can ultimately improve their learning outcomes. This study aims to conduct a literature review on the use of Kahoot in Arabic language learning. The method used in this study is the Systematic Literature Review (SLR). Data were collected by documenting and reviewing all articles discussing Arabic language learning assisted by the Kahoot application published between 2018 and 2024. A total of 13 articles from accredited national journals, obtained from the Sinta and Google Scholar databases using the Publish or Perish application, served as the data sources for this study. The results of the study indicate that Kahoot can be used as one of the teacher innovations and assessments in the Arabic language learning process and can improve learning outcomes, motivation, and student effectiveness in learning Arabic.